Caracterização petrográfica de rochas carbonáticas da Formação Jandaíra com ênfase na resistência mecânica aplicada a construções de grande porte - Silva, Leonardo dos Santos (Universidade Federal do Rio Grande do Norte, 2022)
The Potiguar Basin, on the extreme northeastern of Brazil, includes several rocks related to the opening of the South Atlantic Ocean and fragmentation of the Gondwana supercontinent. During the post-rift stage, several transgressive fluvial-marine sequences deposited in this basin. One of these sequences, the Jandaíra Formation, represents most of the on-shore portion of the Potiguar Basin. The Jandaíra Formation is composed of carbonatic rocks that frequently show karst features, such as caves and dolines. The identification of these features, coupled with petrophysical properties of the rocks, are of great importance for the implementation of wind power plants. In this study, samples from a 20 m deep borehole of Jandaíra Formation's rocks, within Baixa do Feijão I wind power plant, in Jandaíra city, Rio Grande do Norte state, were investigated through petrography. The main features, such as matrix, types of grains and cement, as well as their respective facies, were identified. Three main facies were identified: intraclast peloidal neomorphised dolomitized mudstone, bioclastic dolomitized mudstone and crystalline dolomite. Regarding diagenetic events, the following textures were identified: micritization of intraclasts and bioclasts, blocky mosaic cementation, fringe cementation, compactation with concave/convex or sutured contacts, neomorphism of intraclasts and bioclasts, dolomitization and oxidation. The faciology influences directly on the porosity of these rocks, with a crystalline dolomite being the most porous, with 12% of porosity. In this facies, the porosity occurs mostly as intergrain and intragrain, with high connectivity. On the other facies, the porosity occurs mainly as fractures and vugs related to the dissolution of intraclasts. The 2D electric tomography revealed zones with high and low resistivity, possibly related to fractured carbonates with, respectively, low and high water contents. The data allowed to correlate the petrophysical properties with the minimum conditions for allowing the ...